PERAN ORANG TUA BAPTIS DALAM MENDIDIK DAN MEMBINAANAK BAPTIS (Studi di Desa Tuguis Kecamatan Kao Barat Maluku Utara) - Salapa, Rahap; Purwanto, A.; Waani, Fenny J. (Universitas Sam Ratulangi, 2017)
Godfather is the one of role in the society that chosen according to his/her faith to Jesus Christ and considered spiritually and physically able to nurture and educate a child to have faith in Jesus Christ as God and Savior. This research aims to know the role of the godfather in educating and nurturing godchild. This research used qualitative analysis method while the analysis data technique used data gathering, data reduction, data serving and conclusion based on Miles and Huberman (2001). The research showed that the role of the godfather factually carry out the duty in order educate and nurture the godchild especially in Desa Tuguis Kecamatan Kao Barat.Â Keyword : Role of the Godfather, educate, nurture